Learn Spanish/ An Usborne Introduction. - Irving, Nichole (EDC Publishing Tulsa, 1996)
This provides a thourough grounding in up to date Spanish going beyond essential everyday phrases to help you really come to grips with the language.
Spanish teaching
Spanish language
incl
Keywords: Spanish language. -- Vocabulary. -- Introduction